2020
DOI: 10.1186/s12889-020-09360-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors affecting treatment outcomes for pulmonary tuberculosis in Finland 2007–2014: a national cohort study

Abstract: Background: Major transition in tuberculosis (TB) epidemiology is taking place in many European countries including Finland. Monitoring treatment outcome of TB cases is important for identifying gaps in the national TB control program, in order to strengthen the system. The aim of the study was to identify potential risk factors for non-successful TB treatment outcomes, with a particular focus on the impact of comorbidities. We also evaluated the treatment outcome monitoring system. Methods: All notified micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…We need to improve our treatment programme as for almost one-fifth of our cases MDR-TB treatment was interrupted or the patient transferred to another country during treatment resulting in high risk of treatment interruption. On the other hand, our treatment success rate of 71% among pulmonary MDR-TB cases is close to the rate published earlier for pulmonary non-MDR-TB cases in Finland [ 26 ]. Nevertheless, direct conclusions about MDR versus non-MDR cases cannot be made as demographics among these two cohorts differ substantially; MDR cases are much younger, have less comorbidities and are more often of foreign origin [ 26 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We need to improve our treatment programme as for almost one-fifth of our cases MDR-TB treatment was interrupted or the patient transferred to another country during treatment resulting in high risk of treatment interruption. On the other hand, our treatment success rate of 71% among pulmonary MDR-TB cases is close to the rate published earlier for pulmonary non-MDR-TB cases in Finland [ 26 ]. Nevertheless, direct conclusions about MDR versus non-MDR cases cannot be made as demographics among these two cohorts differ substantially; MDR cases are much younger, have less comorbidities and are more often of foreign origin [ 26 ].…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, our treatment success rate of 71% among pulmonary MDR-TB cases is close to the rate published earlier for pulmonary non-MDR-TB cases in Finland [ 26 ]. Nevertheless, direct conclusions about MDR versus non-MDR cases cannot be made as demographics among these two cohorts differ substantially; MDR cases are much younger, have less comorbidities and are more often of foreign origin [ 26 ].…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings were reported in Australia, ( 6 ) Denmark, ( 12 ) China, Taiwan (China), ( 16 ) Spain, ( 17 ) the Republic of Korea, ( 18 ) the United Kingdom ( 19 ) and Finland. ( 20 ) We also found that a higher proportion of early deaths were TB-specific rather than non-TB-specific, which suggests that patients who survive > 2 months of TB treatment have better outcomes, and late deaths are due more commonly to causes other than TB.…”
Section: Discussionmentioning
confidence: 59%
“…Advanced age is well recognized as a risk factor for morbidity and mortality from TB because of weakening of both the innate and adaptive immune systems. ( 21 ) The presence of comorbidity has also been identified as the most common characteristic of death from TB in other developed countries, such as Australia, ( 6 ) Denmark, ( 12 ) Finland, ( 20 ) the Netherlands, ( 22 ) Spain, ( 17 ) Singapore, ( 23 ) the Republic of Korea, ( 18 ) China, Taiwan (China) ( 9 , 11 , 24 ) and the USA. ( 10 ) Older people tend to be more vulnerable to comorbidity, as suggested by a one-day survey of the prevalence of morbidity in 2017 conducted by random stratified sampling in 6402 hospitals (76% of hospitals in Japan), which showed that the rate of comorbidity among people aged ( 2 )65 years was 17 times higher than among those aged 20–24 years.…”
Section: Discussionmentioning
confidence: 99%
“…Elder age, type of tuberculosis disease, prior tuberculosis cure, very low income, incomplete contact to transport, distance from treatment center to the home, low information about the disease and its dealing, partial public funding, multidrug high resistance, and comorbidity specially with HIV have all been investigated to be associated with ineffective treatment consequences [7][8][9][10][11][12]. The ultimate goal of the strategy to end the global TB epidemic by 2035 is to reduce TB-related deaths by 95% and the prevalence rate of TB by 90% [13,14]. Understanding the factors related to the outcomes of TB treatment is critical.…”
Section: Introductionmentioning
confidence: 99%